Inclusive School: A Case Study of an Elementary School (Conference on English Language Teaching, 2024)
This study focuses on how inclusive education practices are applied in Indonesian classrooms with the goal of meeting the needs of all children, including those with special needs, while also being in line with national educational goals. The study emphasizes the significance of establishing cooperative and encouraging learning environments in conventional educational environments by reviewing literature on inclusive education philosophies and practices, which includes co-teaching approaches. Implementing a descriptive qualitative research approach, data was collected by observations, interviews, and documentation at Lazuardi Kamila Global Compassionate School, serving as a case study representing inclusive education practices in Indonesia. The findings highlight the school's diverse programs and facilities created to meet the requirements of a wide range of students, emphasizing the value of individual attention and cooperative learning strategies. The study emphasizes how important it is to continue researching and developing inclusive education practices in order to guarantee all children equal access to high-quality education and maintain the sustainability and effectiveness of Indonesia's national education system.